Monopoly, money, and you : how to profit from the game's secrets of success - Orbanes, Philip (McGraw-Hill Education, 2013)
Orbanes highlights the financial lessons you can learn when playing the game Monopoly. The legendary game provides opportunities to handle money and practice the art of negotiation, laying the groundwork for sound financial judgment.